The Effect of Competence, Moral Reasoning, Altruism, and Auditor's Locus of Control Behavior on Audit Quality - Kharisma, Hendrick; Qintharah, Yuha Nadhirah (Universitas Islam Kadiri, 2025)
Introduction/Main Objectives: This study aims to analyze the influence of auditor competence, moral reasoning, altruism, and locus of control on audit quality in the Public Accounting Enterprises of Jakarta and Bekasi. Background Problems: Audit quality plays a pivotal role in maintaining public trust and ensuring the integrity of financial reports. Recent cases, such as the audit mismanagement of PT Indosat Tbk, highlight the importance of understanding how individual auditor traits impact audit outcomes. Novelty: While prior research has evaluated each factor individually, this study offers a comprehensive analysis of four psychological and behavioral aspects—competence, moral reasoning, altruism, and locus of control—in shaping audit quality, specifically within Indonesian public accounting firms. Research Methods: A quantitative approach was used by distributing Likert-scale questionnaires to 100 auditors from firms in Jakarta and Bekasi. Data were analyzed using multiple linear regression to determine the effect of each independent variable on audit quality. Finding/Results: The results reveal that auditor competence and moral reasoning significantly and positively affect audit quality. Conversely, altruism has a statistically significant negative effect, indicating that excessive selflessness may compromise objectivity. The locus of control variable showed no significant influence, suggesting that internal or external control beliefs do not necessarily impact audit quality in this context. Conclusion: This study concludes that strengthening auditor competence and moral judgment enhances audit quality, while unchecked altruism may hinder professional skepticism. Research limitation/implications: These findings emphasize the need for targeted training and ethical reinforcement in audit environments. Future research should explore additional behavioral dimensions and expand the geographical scope to validate these results.